Empowerment of mosque communities to increase body immune with aroma therapy robots - Iswanto Suwarno; Nia Maharani Raharja; Alfian Maarif; Gatot Supangkat; Anish Pandey; Cengiz Deniz; Adhianty Nurjanah; Dhiya Uddin Rijalusalam; Carlos Sánchez-López; Irfan Ahmad (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Treatment of patients suffering from infection with the novel corona virus by means of therapy because there is no one drug to cure patients affected by Covid-19. Patients with COVID-19 are undergoing therapy to boost their immune system. One of the therapies to increase the body's immunity is by using aromatherapy. This community empowerment program applies aromatherapy robots to increase the immunity of the congregation who are carrying out worship activities at the mosque. The purpose of this community empowerment is to create and implement an aromatherapy robot that has an aromatherapy liquid level indicator and can refill aromatherapy with liquids from plants. The method of implementing the community empowerment program is as follows. The robot was made by UMY community service staff consisting of nine people who are experts in their respective fields, chaired by Dr., Ir., Iswanto., S.T., M.Eng., IPM who is an expert in robotics. There are members from the University of Muhammadiyah Yogyakarta, University of UIN Sunan Kalijaga Yogyakarta, Ahmad Dahlan University and the University of Tlaxcala, Mexico. There are five members from the University of Muhammadiyah Yogyakarta, namely Dr., Adhianty Nurjanah, S.Sos., M.Sc. expert in disaster communication, Dr. Ir. Gatot Supangkat who is an expert in the field of plants and Dhiya Uddin Rijalussalam., S.T who is an expert in the field of robot assembly. Members from outside UMY are Nia Maharani Raharja., S.T., M.Eng. from the University of UIN Sunan Kalijaga Yogyakarta, an expert in instrumentation, Alfian Maarif., S.T., M.Eng. from Ahmad Dahlan University, an expert in control and Professor Ph.D. Carlos Sánchez-López is an expert in the field of autonomous robots from the University of Tlaxcala, Mexico. With this aromatherapy robot, mosque congregations can increase their immunity by inhaling the aromatherapy in the robot.